2020
DOI: 10.3390/ijerph17155366
|View full text |Cite
|
Sign up to set email alerts
|

Drivers’ Visual Attention Characteristics under Different Cognitive Workloads: An On-Road Driving Behavior Study

Abstract: In this study, an on-road driving experiment was designed to investigate the visual attention fixation and transition characteristics of drivers when they are under different cognitive workloads. First, visual attention was macroscopically analyzed through the entropy method. Second, the Markov glance one- and two-step transition probability matrices were constructed, which can study the visual transition characteristics under different conditions from a microscopic perspective. Results indicate that the fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…From the above analysis, it can be seen that the three indicators of fixation duration, saccade duration, and saccade amplitude are all effective in characterizing the driver’s visual workload on the TSIV [ 41 ]. Therefore, these three eye movement indicators can be combined to form a comprehensive indicator of the driver’s visual workload.…”
Section: Discussionmentioning
confidence: 99%
“…From the above analysis, it can be seen that the three indicators of fixation duration, saccade duration, and saccade amplitude are all effective in characterizing the driver’s visual workload on the TSIV [ 41 ]. Therefore, these three eye movement indicators can be combined to form a comprehensive indicator of the driver’s visual workload.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of visual shock is generally between 0.05 s and 1.00 s at the entrance and exit of the tunnel. To quantify the visual psychological and physiological load of drivers, the converted duration of visual shock is used as an indicator to evaluate the visual load of drivers [ 7 , 13 ], to obtain the visual comfort in the entrance and exit sections, as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Kim [ 12 ] found that panning is the only touch gesture that can be used without negative consequences when operating in-vehicle information systems with visual occlusion while driving. Ma [ 13 ] investigated the visual attention fixation and transition characteristics of drivers under different cognitive workloads. Bitkina [ 14 ] believed that Gaze point, duration, fixation, and pupil diameter significantly influence driving workload.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The new results presented in this study suggest that the addition of distractors in the ADEMd enhances the assessment potential of the test concerning visual processing speed and divided and selective attention, with these abilities being relevant for proper driving [ 27 , 50 , 51 ]. This can be seen in the positive correlation encountered only in the drivers between the horizontal time with distractors (Hd adj ) and the three subtests of the UFOV (see Table 3 ).…”
Section: Discussionmentioning
confidence: 99%